Water- borne protozoan parasitic infections - J. S. Edirisinghe (Journal of the College of Community Physicians, 2002)
Contamination of drinking water by human and animal excreta is a major public health problem the world over. A number of serious protozoan parasitic infections are transmitted to humans by way of contaminated drinking water. Water used by humans for purposes other than drinking such as washing, bathing, swimming, recreational and irrigation activities could also transmit waterborne parasitic pathogenic agents resulting in disease.   Pathogenic protozoan parasitic agents that could be transmitted by drinking water are, Entamoeba histolytica, Giardia intestinal Cryptosporidium parvum, Isospora belli, Blastocystis hominis, Cyclospora cayetanensis and Microsporidia. Naegleria fowleri and Acanthamoeba spp. are generally associated with water related recreational activities.   The review includes a brief historical account, clinical features and the mode of exposure / association with water, under each parasite listed.